Organ-Specific Antioxidant, Antibacterial, and α-Amylase Inhibitory Activities of Hydroethanolic Extracts from Grewia monticola Sond. - Ananias Nhanrave; Paulo José Cumbane; Rui Raice (Natural Resources for Human Health, 2026)
Plants of the genus Grewia are widely used in traditional medicine and are recognized as important sources of bioactive secondary metabolites. However, the biological potential of Grewia monticola remains poorly explored. This study investigated the phytochemical composition, antioxidant capacity, antibacterial activity, and α-amylase inhibitory potential of hydroethanolic extracts obtained from the leaves, stem, and roots of Grewia monticola. Qualitative phytochemical screening and spectrophotometric quantification of total phenolic compounds (TPC), total flavonoid content (TFC), and total tannin content (TTC) were performed. Antioxidant activity was evaluated using DPPH radical scavenging, ferric reducing power (FRP), and phosphomolybdenum total antioxidant capacity (TAC) assays. Antibacterial activity was assessed by the disk diffusion method against Staphylococcus aureus, Salmonella typhimurium, Escherichia coli, and Enterococcus faecalis. α-Amylase inhibitory activity was determined using the 3,5-dinitrosalicylic acid (DNS) method. The extracts contained phenolics, flavonoids, and tannins with clear organ-specific distribution. Leaves exhibited the highest phenolic content, whereas stem extracts contained the highest levels of flavonoids and tannins. All extracts showed concentration-dependent antioxidant activity across all three assays. Antibacterial tests revealed notable inhibition of both Gram-positive and Gram-negative bacteria, with stem extracts producing the largest inhibition zones. In the α-amylase inhibition assay, root extracts showed the strongest activity (IC₅₀ < 10 μg/mL), followed by leaves (30.10 ± 0.92 μg/mL) and stem (48.48 ± 1.54 μg/mL), all surpassing the positive control acarbose (IC₅₀ = 63.57 ± 3.85 μg/mL). Overall, G. monticola represents a promising natural source of multifunctional bioactive compounds with antioxidant, antibacterial, and antidiabetic potential, warranting further phytochemical characterization and in vivo investigation.